Effects of cascading hydropower dams on the composition, biomass and biological integrity of phytoplankton assemblages in the middle Lancang-Mekong River - Li, Jinpeng; Dong, Shikui; Liu, Shiliang; Yang, Zhifeng; Peng, Mingchun; Zhao, Chen (Ecological engineering, 2013)
•The phytoplankton assemblages were investigated before and after cascading dams.•The phytoplankton assemblages were sensitive in the aquatic ecosystem.•The P-IBI showed the biological integrity associated with cascading dams.•The habitat and longitudinal connectivity of river were destroyed by cascading dams.•Cascading dams can induce accumulation effect on the aquatic ecosystem. Planning for extensive cascading hydropower dam exploitation in the southwest of China has been the subject of debate and conflict in recent years. The middle reach of the Lancang-Mekong River, a typical region for cascading hydropower dam construction, was selected as a study area to explore the composition, biomass and biological integrity of phytoplankton assemblages before and after such construction. Sampling sites along the longitudinal gradient of this river were chosen to measure phytoplankton assemblages in 1988 (pristine state), 1997 (completion of the first dam), and 2011 (cascading dams). The results indicated that composition and abundance were greatly altered by the construction and operation of cascading dams. The phytoplankton assemblages were found to be sensitive indicators in the assessment of aquatic ecosystem health degradation associated with cascading dams. The phytoplankton index of biotic integrity (P-IBI) was developed as a comprehensive and quantitative index to assess the variation in biological integrity and aquatic ecosystem degradation before and after the construction of cascading dams. The effects of the cascading dams on the aquatic ecosystem were serious and more complex than the effects of a single dam. The ecological and longitudinal connectivity of the aquatic ecosystem and the natural diversity of aquatic habitats transitioned in several impoundment areas due to the influence of the cascading dams. Increasing abundance and biomass of phytoplankton assemblages in reservoir areas can lead to degradation of the aquatic ecosystem compared with natural riverine ecosystems. Cascading hydropower dams can cause cascades and accumulation effects on the riverine ecosystem.